Strategi Promosi Wisata Lokal Melalui Media Sosial Di Sagara View Karangbolong Kabupaten Kebumen - Wita Diana Rismawati; Sujiono Sujiono; Ayuning Wulan (Tamasya : Jurnal Pariwisata Indonesia, 2024)
This study aims to describe the utilization of social media as a local tourism promotion strategy at Sagara View Karangbolong Kebumen Regency and describe the obstacles and challenges faced in implementing the Local Tourism Promotion Strategy through Social Media at Sagara View Karangbolong Kebumen Regency. The research method used is descriptive qualitative, which allows an in-depth understanding of the promotional approach applied by the manager of the tourist destination. Data was collected through interviews with managers, businesses and visitors, observation and documentation, as well as the official social media content of Sagara View Karangbolong. The results showed that positive results towards the utilization of social media as a means of promotion. Sagara View Karangbolong uses social media facilities in the form of Tiktok and Instagram applications for its promotional media. By utilizing hours that have high traffic, and using influencer intermediaries, as well as innovating more interesting content and utilizing the stories feature, it is proven that it can increase the interest and number of tourists visiting Sagara View Karangbolong.